KAJIAN MASALAH PEMBANGUNAN WILAYAH DALAM PENGELOLAAN HUTAN LINDUNG MUTIS TIMAU - Fransiskus Xaverius Dako (Politeknik Pertanian Negeri Kupang, 2013)
A Study of area development issues onmanagement of the protected Mutis-Timau Forest. This study was aimed to identify and to formulate problems triggering forest damage in The Mutis Timau. This study used basic method of descriptive analysis. It was taken in area protected forest and Fatumnasi village close to the protected forest. Data collected were social-economic data and government regulations within the authority of Mutis Timau protected forest management. Data then descriptively analyzed to identify problems causing damage on Mutis Timau protected forest. The result suggested that problems causing damage on Mutis Timau protected forest werehunger (lack of rice) for Fatumnasi farmers (45,581 kg/year), a poor harvest in agricultural farm (13,717 kg), low income in Fatumnasi village (when converted into rice value it remained being categorized as poor (306 kg), lack of fire wood supplywhich come from agricultural farm in Fatumnasi village (8.941 m3), lack offeedsupply in Fatumnasi village (1420 kg/day), land deficit (140.76 ha or 0.34/household), and lack of government’s regulation about a suitable scheme for the governance of Mutis Timau protected forest.Keywords: Problems, Management, Protected forest